1, 2-Disubstituted ferrocenyl water-soluble selenoether and telluroether ligands and their palladium (II) complexes: CV and variable temperature NMR studies. (15th November 2022) - Villamizar C, Claudia P.; Sharma, Pankaj; Anzaldo, Bertin; Gonzalez, Rodary; Gutierrez, Rene; Kumar, Arun
Graphical abstract: Synthesis of new 1, 2 disubstituted ferrocenylated selenoether and telluroether ligands, that contain other donor groups Oxygen and Nitrogen and their respective palladium complexes were synthesized. The ligands and their palladium complexes were characterized by elemental analysis, ( 1 H, 13 C, 77 Se or 125 Te) NMR, variable temperature NMR studies and IR, UV–vis spectroscopy, mass spectrometry, and cyclic voltammetry. The molecular structures of all the palladium complexes were determined by X-ray crystallography which confirms that these ligands act in a bidentate fashion. Abstract: The 1, 2 disubstituted ferrocenylated unsymmetrical potentially tridentate selenoether and telluroether ligands, containing Oxygen and Nitrogen at the other donor sites and their respective palladium complexes were synthesized. The molecular structures of all the palladium complexes were determined by X-ray crystallography which confirms that these ligands coordinate in a bidentate fashion. The structures show intramolecular and intermolecular interactions type E···E, E···O, CH···Cl, and E···Cl interactions (E = Se or Te). Interestingly chalcogenoether ligands containing the 3-hydroxy propyl group and their palladium complexes are soluble in water and 1 H NMR spectra of these ligands do not show OH proton signal at room temperature but at low temperature broad deshielded proton signal confirms the involvement of –OH group in secondary interactions with Se or Te atom as an intramolecular chalcogen bonding. The cyclic voltammograms of selenoether and their complexes present single reversible and quasi reversible waves while telluroether ligands present three quasi reversible processes and their complexes show three nonreversible redox processes.